RANCANG BANGUN UNIT PENGERING HIBRIDA HEMAT ENERGI UNTUK PENGERINGAN TEMBAKAU RAJANGAN - A. Sutowo Latief; Totok Prasetyo; Suparni Setyawati Rahayu (JURNAL LITBANG PROVINSI JAWA TENGAH, 2011)
The general objective of this research is to design and making hybrid dryer unit is used drying the chopped tobacco, in particular is to examine the performance of the hybrid dryer, the temperatures found in each rack, and compare the results of drying tobacco with naturally dried tobacco or dried above the traditional rack. This research method by creating a hybrid construction of the dryer unit, as follows: (1) determining the size of the design of space heating, (2) determining the size of the rack and the many levels of shelving, (3) purchasing of necessary materials and equipment, (4) implementation of manufacturing components or major parts of the dryer according to its function, (5) assembling the components into the dryer construction. This study focus are the performance of the hybrid dryer unit that has been created, namely: (1) homogeneity of dried tobacco content of each rack, (2) production capacity of each generation, (3) a long drying process, (4) operational costs and financial analysis. The results of this study is a prototype unit of a viable hybrid dryer used to dry tobacco with a capacity of 50 kg of chopped wet tobacco to produce 10 kg of dried tobacco drying time is 18 hours. Hybrid dryer unit is fit for use based on the analysis of the structure of production and financial feasibility analysis based on investation of hybrid dryer Rp 15.000.000 and working capital Rp 10.000.000. The method of Net Present Value (NPV) = Rp 48.747412, Internal Rate of Return (IRR) = 60%, Net Benefit Cost Ratio (Net B / C) = 2, 95, and Pay Back Period (PBP) = 1.16 years.